Artificial intelligence and the state: Seeing like an artificial neural network - Petter Törnberg; Ola Söderström; Jennifer Barella; Saskia Greyling; Sophie Oldfield (Big Data & Society)
The emergence of the modern state was closely intertwined with the advent of statistics and demographic data. Today, we are witnessing the ascent of artificial intelligence as a new technology of governance. This article seeks to lay the groundwork for a research agenda at the intersection of the state and artificial intelligence, unpacking the notion of “AI” and examining the consequences of the state transitioning from statistics to artificial intelligence as the means of “seeing” its subjects. The first part of the article argues that artificial intelligence represents a fundamental epistemic shift: from variables to patterns , from rules to associations , from surveys to sensors . This transition may transform governance and biopolitics, and with them, the very meanings of concepts such as citizenship, democracy, and population. In the second part of the article, the article draws on the literature on socio-technical transitions to conceptualize the integration of artificial intelligence into state practices, offering a framework to guide empirical research on how artificial intelligence is transforming governance.